2012
DOI: 10.1007/s11103-012-9955-5
|View full text |Cite
|
Sign up to set email alerts
|

A TFIIIA-type zinc finger protein confers multiple abiotic stress tolerances in transgenic rice (Oryza sativa L.)

Abstract: The TFIIIA-type zinc finger transcription factors are involved in plant development and abiotic stress responses. Most TFIIIA-type zinc finger proteins are transcription repressors due to existence of an EAR-motif in their amino acid sequences. In this work, we found that ZFP182, a TFIIIA-type zinc finger protein, forms a homodimer in the nucleus and exhibits trans-activation activity in yeast cells. The deletion analysis indicated that a Leu-rich region at C-terminus is required for the trans-activation. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 54 publications
3
77
0
Order By: Relevance
“…Although the roles of some C2H2-type zinc finger proteins have been identified to be related to stress and developmental processes, the functions of C2H2-type ZFPs from rice involved in stress response are largely unknown (Sun et al 2010;Huang et al 2012). In this study, as a novel C2H2-type zinc finger protein gene, OsMSR15 was cloned from rice and then functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of some C2H2-type zinc finger proteins have been identified to be related to stress and developmental processes, the functions of C2H2-type ZFPs from rice involved in stress response are largely unknown (Sun et al 2010;Huang et al 2012). In this study, as a novel C2H2-type zinc finger protein gene, OsMSR15 was cloned from rice and then functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ZFP252 represents another candidate for engineering crop plants with enhanced tolerance to salt and drought stresses [107]. In a recent addition to this research field, the EAR-motif containing C2H2 ZF ZFP182 from rice was shown to mediate salt, cold, and drought tolerance [108]. …”
Section: Large Plant Tf Families In Abiotic Stress Responsesmentioning
confidence: 99%
“…The seeds were then placed in Petri dishes (diameter is 9 cm) with two sheets of filter paper, and added 20 mL solution. Seeds were germinated under normal (sterile distilled water), drought (15 % PEG-6000) and salt (150 mM NaCl) conditions according to Fu et al (2012) and Huang et al (2012) methods respectively at 30 ± 1°C for 10 days with a 12 h light/12 h dark photoperiod in growth chamber. The solution was replaced every 2 days.…”
Section: Seed Germination Evaluationmentioning
confidence: 99%
“…The number of normal seedling was counted to calculate the seedling survival percentage (SSP) at the three-leaf stage under normal condition. After that, the weak and dead plants were removed, and *20 healthy seedlings per accession were retained for stress treatments according to Huang et al (2012) methods with minor modifications. Seedlings were treated without irrigation for 14 days for drought stress treatment, and seedlings were grown in 150 mM NaCl solution for 14 days and the solution was refreshed every 2 days for salt stress treatment.…”
Section: Seedling Survival Evaluationmentioning
confidence: 99%